An experimental investigation and correlation of the viscosity refrigerant/oil solutions. (January 2021) - Sun, Yanjun; Wang, Jian; Wang, Xiaopo; He, Maogang; Hu, Yusheng
Abstract: 2, 3, 3, 3-tetrafluoroprop-1-ene (R1234yf) and trans-1, 3, 3, 3-tetrafluoropropene (R1234ze(E)) as the promising refrigerants have attracted wide attention. To understand better of the refrigeration-cycle performance working with new refrigerants, the thermodynamic properties of refrigerant/oil mixtures should be well known, especially the viscosity of the refrigerant/oil mixture. Using a dual-capillary method, the viscosities were measured for POE75 saturated with R1234yf and R1234ze(E) from 303.15 to 348.15 K. The viscosity trends of R1234yf/POE75 and R1234ze(E)/POE75 mixtures are similar. As rising solubility, a sharp decrease of viscosity appeared firstly, and then it goes to be flat. Results show that the dissolved refrigerant in oil largely reduces the oil viscosity. Comparing to viscosity models including an empirical model (modified Setchenow-type equation) and Eyring's absolute rate theory coupled with three excess Gibbs energy models (Eyring-MTSM model, Eyring-NRTL model, and Eyring-wilson model), the Eyring-MTSM model give better results than the other studied models.